Association of insulin-like growth factor I gene polymorphisms (IGF1/TasI and IGF1/SnaBI) with the growth and subsequent milk yield of Polish Holstein-Friesian heifers - M. Szewczuk; M. Bajurna; S. Zych; W. Kruszyński (Czech Journal of Animal Science, 2013)
The aim of this study was to estimate potential relationships between insulin-like growth factor I gene polymorphisms (IGF1/TasI and IGF1/SnaBI) and the growth parameters of calves as well as their subsequent milk performance. The study involved a total of 191 Polish Holstein-Friesian var. Black-and-White calves. Both polymorphic sites were determined with Amplification Created Restriction Sites-Polymerase Chain Reaction (ACRS-PCR). In the case of the IGF1/SnaBI polymorphism, the genotype and allele frequencies were as follows: TT - 0.27, CT - 0.55, CC - 0.18, T - 0.54, and C - 0.46. The CC genotype was favourable and associated with higher body weight at the 2nd month of age of calves (WT60) and their daily body weight gains from the 1st to the 2nd month (P ≤ 0.05) as well as subsequent milk, fat, and protein yield (P ≤ 0.01). For the IGF1/TasI polymorphism, the highest frequency of the AA genotype (0.69) was found. Allele frequencies were 0.75 and 0.25 for the A and C alleles, respectively. In the association study, the AC genotype was significantly associated with higher WT60 and average daily gains in the periods from the 2nd to the 3rd month of age and for the whole rearing period (P ≤ 0.05) as well as subsequent milk, fat, and protein yield (P ≤ 0.01). Combined genotypes were also included into the analysis. The highest yields of milk as well as fat and protein were found in cows with the CC/AA combination. No clear relationships between body weight and genotype combination were found.